Taxonomy of Bassinae (=Agathidinae Nees 1814) Nees 1812 in Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Two genera of Bassinae (Hymenoptera: Braconidae) have been described and illustrated from Bangladesh and a key was prepared. The genera are: Agathis Latreille and Bassus Fabricius newly recorded from Bangladesh. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17239 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):135-146, 2011